2020
DOI: 10.1038/s41467-020-16991-2
|View full text |Cite
|
Sign up to set email alerts
|

Silencing hepatic MCJ attenuates non-alcoholic fatty liver disease (NAFLD) by increasing mitochondrial fatty acid oxidation

Abstract: Nonalcoholic fatty liver disease (NAFLD) is considered the next major health epidemic with an estimated 25% worldwide prevalence. No drugs have yet been approved and NAFLD remains a major unmet need. Here, we identify MCJ (Methylation-Controlled J protein) as a target for non-alcoholic steatohepatitis (NASH), an advanced phase of NAFLD. MCJ is an endogenous negative regulator of the respiratory chain Complex I that acts to restrain mitochondrial respiration. We show that therapeutic targeting of MCJ in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 50 publications
5
92
1
Order By: Relevance
“…Although research is paving the way for the development of therapeutics, the results of early clinical trials of drugs targeting single pathways have been mostly unsuccessful. Combining compounds that reduce lipid accumulation and hepatocellular injury has been proposed as a more suitable therapeutic strategy for this complex disease (Barbier-Torres et al, 2020;Barbier-Torres et al, 2017;Ertunc & Hotamisligil, 2016). Targeting multiple pathways is more likely to translate into successful outcomes (Friedman et al, 2018;Mardinoglu et al, 2018a;Mardinoglu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although research is paving the way for the development of therapeutics, the results of early clinical trials of drugs targeting single pathways have been mostly unsuccessful. Combining compounds that reduce lipid accumulation and hepatocellular injury has been proposed as a more suitable therapeutic strategy for this complex disease (Barbier-Torres et al, 2020;Barbier-Torres et al, 2017;Ertunc & Hotamisligil, 2016). Targeting multiple pathways is more likely to translate into successful outcomes (Friedman et al, 2018;Mardinoglu et al, 2018a;Mardinoglu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, an approach that safely attenuates ETC without a full blockage could be more appropriate as a potential therapeutic. MCJ is the first identified endogenous negative regulator of Complex I and mitochondrial respiration, and it is abundantly expressed in some of the highly metabolically active tissues (e.g., liver, heart) 27 , 28 . Since the absence of MCJ causes chemoresistance, we investigated whether MCJ mimetics could restore MCJ function as a brake on the ETC in chemoresistant cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we show that ATP from glycolysis is dispensable, therefore upregulation of mitochondrial metabolism contributes to this mechanism of chemoresistance. Methylationcontrolled J protein (MCJ) encoded by the DNAJC15 gene, localizes on the inner membrane of mitochondria and acts as an endogenous brake on mitochondrial respiration by negatively regulating Complex I [25][26][27][28] . Retrospective and prospective studies have shown that loss of MCJ expression in tumors correlates with chemotherapy resistance and poor prognosis in breast and ovarian cancer patients 29,30 .…”
mentioning
confidence: 99%
“…Inhibition of hepatic MCJ helps alleviates the inhibitory effect on ETC and prevents lipid accumulation. However increased beta-oxidation was associated with the accumulation of ROS which can lead to NAFLD progression, however, the activation of ETC diverts the ROS into the production of respiratory complexes reducing the damage caused due to ROS [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Barbier-Torres et al designed a small interfering ribonucleic acid (SiRNA) and a liver-specific delivery system to silence the MCJ and demonstrate the above-mentioned findings. His study also demonstrated that MCJ levels are higher in the hepatocytes of patients with NAFLD compared to healthy patients [ 39 ].…”
Section: Reviewmentioning
confidence: 99%